A Sensitive, Stability indicating UPLC method for the identification and characterization of forced degradation products for Drometrizole Trisiloxane through MSn studies - M. Ajay Babu & , G. V. Krishna Mohan, J. Satish, Pradipbhai D. Kalariya, CH. Krishnam Raju & , Sharad D. Mankumare (Journal of Applied Pharmaceutical Science, 2018)
A rapid, simple and reliable gradient ultra performance liquid chromatography combined with tandem mass spectrometry method was developed and validated for separation, recognition, and characterization of forced degradation products for Drometrizole Trisiloxane. As per International Conference on Harmonization guidelines, the drug was exposed to acidic, basic, photolytic, oxidative and thermal conditions. The main drug shows extensive degradation towards stress conditions such as acid and base hydrolysis. The three degradation products were identified. The chromatographic separation was achieved through the C8 column 2.1 × 100, 1.8 μm) from linear gradient elution and the wavelength detection was set at 305 nm for drug and its forced degradation products. The parameters such as specificity, linearity, accuracy, precision, and robustness were used for validation of the method. The sequential pathway for the fragments was achieved through the acquired mass spectra from drug and its degradation products through LC/MS/MS studies. Accurate masses of drug and its degradation products were confirmed through LC-MS/Q-ToF analysis. Degradation products were characterized by comparing with the pattern of drug molecule fragmentation.
Keywords: Drometrizole Trisiloxane, Stability indicating, UPLC, Degradation Products, Characterization, LC-MS/ MS.